CAMELS-CH: hydro-meteorological time series and landscape attributes for 331 catchments in hydrologic Switzerland - M. Höge; M. Kauzlaric; M. Kauzlaric; R. Siber; U. Schönenberger; P. Horton; P. Horton; J. Schwanbeck; M. G. Floriancic; D. Viviroli; S. Wilhelm; A. E. Sikorska-Senoner; et al. (Earth System Science Data, 2023)
We present CAMELS-CH (Catchment Attributes and MEteorology for Large-sample Studies – Switzerland), a large-sample hydro-meteorological data set for hydrologic Switzerland in central Europe. This domain covers 331 basins within Switzerland and neighboring countries. About one-third of the catchments are located in Austria, France, Germany and Italy. As an Alpine country, Switzerland covers a vast diversity of landscapes, including mountainous environments, karstic regions, and several strongly cultivated regions, along with a wide range of hydrological regimes, i.e., catchments that are glacier-, snow- or rain dominated. Similar to existing data sets, CAMELS-CH comprises dynamic hydro-meteorological variables and static catchment attributes.